2014
DOI: 10.3233/ves-140509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral vitamin C on histamine levels and seasickness

Abstract: BACKGROUND: Seasickness is a risk aboard a ship. Histamine is postulated as a causative agent, inversely related to the intake of vitamin C. Persons with mastocytosis experienced improvement of nausea after the intake of vitamin C. OBJECTIVE: To determine whether vitamin C suppresses nausea in 70 volunteers who spent 20 minutes in a life raft, exposed to one-meter-high waves in an indoor pool. METHOD: Double-blind placebo-controlled crossover study. Two grams of vitamin C or placebo was taken one hour before e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A protein‐predominant beverage taken 5 or 30 min before optokinetic stimulation was found to be effective in suppressing gastric tachyarrhythmia and MS symptoms . A recent double‐blind, placebo‐controlled crossover study found that vitamin C was effective in suppressing symptoms of seasickness, particularly in youngsters .…”
Section: Nonpharmacological Countermeasuresmentioning
confidence: 99%
“…A protein‐predominant beverage taken 5 or 30 min before optokinetic stimulation was found to be effective in suppressing gastric tachyarrhythmia and MS symptoms . A recent double‐blind, placebo‐controlled crossover study found that vitamin C was effective in suppressing symptoms of seasickness, particularly in youngsters .…”
Section: Nonpharmacological Countermeasuresmentioning
confidence: 99%
“…It has been documented that the residents of the Samoa islets consumed one or two mangoes prior to their sailing trips to prevent sea sickness [ 123 ]. This could be attributed to the high levels of polyphenols [ 124 ] and ascorbic acid (vitamin C) in mangoes [ 124 , 125 ].…”
Section: Interventions For Mitigating Motion Sicknessmentioning
confidence: 99%
“…Vitamin C was used as an adjuvant to correct the HI. A daily dose of 300–500 mg enhanced histamine degradation and inhibited mast cell degranulation [ 127 ]. Natural flavonoids (fisetin, kaempferol, quercetin, rutin, and luteolin) and the active alkaloid berberine inhibit mast cell degranulation in vitro [ 128 ].…”
Section: Principles Of Treatment For Histamine Intolerancementioning
confidence: 99%